Characteristics of geologic materials and formations : a field guide for geotechnical engineers - Hunt, Roy E. (CRC/Taylor & Francis, 2007)
Properly understanding and characterizing geologic materials and formations is vital for making critical engineering decisions. Identifying and classifying rock masses and soil formations allows reasonable estimation of their characteristic properties. Comprising chapters from the second edition of the revered Geotechnical Engineering Investigation Handbook, Characteristics of Geologic Materials and Formations provides a basis for recognizing, identifying, and classifying the various rock and soil types. With clear, concise, and hands-on guidance, this book describes these rock and soi.
Keywords: Engineering geology -- Handbooks, manuals, etc.; elektronické knihy; electronic books